‘Ulster’s policing goes global’: the police reform process in Northern Ireland and the creation of a global brand - Ellison, Graham (Crime, law and social change, 2008)
This paper engages with contemporary discussions in relation to the commodification of policing and security. It suggests that the existing literature regarding these trends has been geared primarily towards commercial security providers and has failed to address the processes by which public policing models are commodified and marketed both within, and through, the transnational policing community. Drawing upon evidence from the police change process in Northern Ireland, we argue that a Northern Irish Policing Model (NIPM) has emerged in the aftermath of the Independent Commission on Policing (ICP) reforms. This is increasingly branded and promoted on the global stage. Furthermore, we suggest that the NIPM is not monolithic, but segmented, and targeted towards a number of different ‘consumers’ both domestically and transnationally. Reflecting these diverse markets, the NIPM draws upon two seemingly incongruous constituent elements: the ‘best practice’ lessons of policing transition, as embodied in the ICP reforms; and, the legacy of counter-terrorism expertise drawn from the preceding decades of conflict. The discussion concludes by querying as to which of these components of the NIPM is in the ascendancy.